2001
DOI: 10.1159/000050510
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Restrictive Spirometric Pattern in Older Thalassemic Patients

Abstract: Background: Lung impairment represents one of the complications of thalassemia major whose clinical picture can remain in subclinical form all life long. Few works have been published and the results are contradictory. Objectives: The aim of this study was to determine the spirometric pattern, the age of onset in thalassemic boys and girls, and to investigate the association with the onset of endocrinological complications. Methods: We studied 48 patients, divided into three groups according to pubertal stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
19
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 21 publications
6
19
1
4
Order By: Relevance
“…Among the thalassemic subjects, restrictive lung function abnormality was the most common (42/63) observation documented in this study. Our findings are consistent with those of Carnelli et al, 1 Factor et al, 2 Tai et al, 5 Luyt et al, 6 and Filosa et al 7 What is unique to our study is that it was performed exclusively in children, while those studies mentioned earlier were all performed in both children and adults, with a considerably older mean age. Therefore, our study shows that lung dysfunction in thalassemic patients has occurred since childhood.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Among the thalassemic subjects, restrictive lung function abnormality was the most common (42/63) observation documented in this study. Our findings are consistent with those of Carnelli et al, 1 Factor et al, 2 Tai et al, 5 Luyt et al, 6 and Filosa et al 7 What is unique to our study is that it was performed exclusively in children, while those studies mentioned earlier were all performed in both children and adults, with a considerably older mean age. Therefore, our study shows that lung dysfunction in thalassemic patients has occurred since childhood.…”
Section: Discussionsupporting
confidence: 93%
“…However, no correlation was found between serum ferritin levels and any of the lung function values. This finding supported those discovered by Tai et al, 5 and Luyt et al 6 , but contrasted with studies by Carnelli et al, 1 Factor et al, 2 and Filosa et al 7 It is suggested that the duration of iron overload may be more important than the actual amount of iron provided through transfusions. 2 Moreover, serum ferritin levels change during the process of chelation, and do not necessarily reflect total body iron stores.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As shown in the studies of Filosa et al 7 and Fung et al, 8 older thalassemia patients with an average age of 19±1.4 years had more RI than younger patients with average age of 10.8±1.7 years and 15.7±1.1 years did. Nevertheless, both SP and NSP in our study were older than those in the previous studies.…”
Section: Discussionmentioning
confidence: 81%